2023
DOI: 10.4012/dmj.2022-214
|View full text |Cite
|
Sign up to set email alerts
|

Bone augmentation with a prototype coral exoskeleton-derived bone replacement material applied to experimental one-wall infrabony defects created in alveolar bone

Abstract: Bone regeneration requires cells, growth factors, and scaffolds that should have biocompatibility, porosity, and physical strength. Therefore, coral granules (CG) with diameters of 600-1,000 µm were prepared as a potential graft material from cultured edaphic thermostable corals. X-ray and electron microscopy characterization revealed that CGs were porous and permeable with lumen diameters of approximately 200 µm. Human periodontal ligament fibroblasts showed significantly increased mitochondrial activity in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Each species of coral naturally offers distinct pore sizes with varying levels of interconnectivity, thereby providing a bespoke capacity support blood vessel ingrowth, nutrient exchange, cell attachment/proliferation, weight bearing capacity and degradation profile to compliment the intended application [ 16 ]. A variety of coral genera, such as Porites [ [17] , [18] , [19] ], Goniopora [ 16 ], Madrepora [ 20 ], Pocillopora [ 21 , 22 ], Montipora [ 23 ] and Acropora [ 24 ] have been characterized for their physical and osteogenic properties, resulting in the launch of wild-harvested clinically approved grafting products such as Biocoral, Pro-osteon and Interpore [ 25 ]. Published reports comparing the resorption rates of naturally occurring Porites, Goniopora, Favites, Lobophyllia and Acropora scaffolds in both orthotopic and ectopic sites concluded that the resorption rate was dictated by the scaffold's porosity volume, calcium density and grafting location [ 13 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each species of coral naturally offers distinct pore sizes with varying levels of interconnectivity, thereby providing a bespoke capacity support blood vessel ingrowth, nutrient exchange, cell attachment/proliferation, weight bearing capacity and degradation profile to compliment the intended application [ 16 ]. A variety of coral genera, such as Porites [ [17] , [18] , [19] ], Goniopora [ 16 ], Madrepora [ 20 ], Pocillopora [ 21 , 22 ], Montipora [ 23 ] and Acropora [ 24 ] have been characterized for their physical and osteogenic properties, resulting in the launch of wild-harvested clinically approved grafting products such as Biocoral, Pro-osteon and Interpore [ 25 ]. Published reports comparing the resorption rates of naturally occurring Porites, Goniopora, Favites, Lobophyllia and Acropora scaffolds in both orthotopic and ectopic sites concluded that the resorption rate was dictated by the scaffold's porosity volume, calcium density and grafting location [ 13 , 26 ].…”
Section: Introductionmentioning
confidence: 99%